1982
DOI: 10.1021/bi00268a007
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of oxygen exchange at the anomeric carbon atom of D-glucose and D-erythrose using the oxygen-18 isotope effect in carbon-13 nuclear magnetic resonance spectroscopy

Abstract: The 18O isotope induced shift in 13C nuclear magnetic resonance (NMR) spectroscopy affords a new and convenient method for the study of oxygen exchange at the anomeric carbon atom of simple sugars. The efficacy of the technique was confirmed by a study of the oxygen exchange reaction of D-[1-13C] glucose. At pH 7.0 and 61 degrees C, the incorporation of 18O from solvent H2(18)O onto the C-1 carbon atom of the diastereomeric alpha- and beta-pyranose sugars was followed by 13C NMR spectroscopy in a continuous as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…29) may be present in linear or cyclic furanose forms. Aqueous solution NMR studies [228,229] have shown that furanose forms (25% and 65% of α and β furanose forms, respectively) are in equilibrium with an appreciable amount of acyclic forms. The five-membered ring structures contain an asymmetric carbon C 1 which leads to the appearance of two stereochemical α and β anomeric species, according to the position of the anomeric OH group (see Fig.…”
Section: Sugars: D-erythrosementioning
confidence: 99%
“…29) may be present in linear or cyclic furanose forms. Aqueous solution NMR studies [228,229] have shown that furanose forms (25% and 65% of α and β furanose forms, respectively) are in equilibrium with an appreciable amount of acyclic forms. The five-membered ring structures contain an asymmetric carbon C 1 which leads to the appearance of two stereochemical α and β anomeric species, according to the position of the anomeric OH group (see Fig.…”
Section: Sugars: D-erythrosementioning
confidence: 99%
“…29) may be present in linear or cyclic furanose forms. Aqueous solution NMR studies [228,229] have shown that furanose forms 378 J.L. Alonso and J.C. L opez (25% and 65% of α and β furanose forms, respectively) are in equilibrium with an appreciable amount of acyclic forms.…”
Section: Monosaccharidesmentioning
confidence: 99%
“…with the solvent, provide an in-depth understanding of protein structure. In a last part, it is shown how conformationselective spectroscopy is able to document the diversity of the PES landscape of 228 E. Gloaguen and M. Mons these species, thus revealing their flexibility. It is also shown how coupling IR and UV information enables spectroscopists to target conformer-selective photophysics in peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, aldoses whose aqueous solutions contain an appreciable amount of hydrate form at equilibrium (e.g., aldotetroses 37 ) undergo 0-1 exchange more readily than aldoses whose aqueous solutions contain minor amounts (e.g., aldohexoses). The rate and extent of exchange at 0-1 can be monitored by 1 3 C NMR spectroscopy by observing of the oxygen isotope effect on the chemical shift of C-l. 38 …”
Section: General Strategymentioning
confidence: 99%